EFL LEARNERS – FACED PROBLEMS IN LISTENING COMPERHENSION - Seli Siti Syadiah (University of Kuningan, 2016)
This research focuses on the EFL learners’ problems in listening comprehension. The present research attempts to investigate listening problems encountered by a group of low level at seniors of a private university in Kuningan. This qualitative case study involved 10 participants who took TOEFL course in 7th semester. The data was gathered by means of questionnaires and interviews. The result of the research showed that accent, pronunciation, speed of speech, insufficient vocabulary, different accent of speakers, lack of concentration, anxiety, and bad quality of recording were the major listening comprehension problems encountered by EFL students. This research also found that most students (60%) used compensation strategy to overcome the problems by guessing the answer, while the others (30%) used memory strategy by using their knowledge or experiences, and the rest 10% of the students used affective strategy by motivating themselves to try answering the questions. Knowing students’ learning difficulties may enable EFL teachers to develop the effective learning strategies and ultimately improve their English listening abilities. Suggestion is made for addressing problems regarding how students can help themselves and the teachers can help their students to overcome the listening comprehension problems encountered by the students.Keywords: EFL Learner, listening comprehension, listening problem